WORKSHOP PENYUSUNAN LAPORAN PTK DAN PENULISAN ARTIKEL PARAFRASIS PADA GURU DI SD UTAMA 2 KOTA TARAKAN - sucahyo mas'an al wahid; Fadhlan Muchlas Abrori; Roby Zulkarnain Noer; Kartini; Ady Saputra (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2022)
The dynamics of education and current tasks carried out by teachers seem increasingly difficult if faced individually without involving collaboration, especially in working through scientific writing. Pramsari in the pulpit of the school journal volume 3 of 2016 said that teachers are the spearhead in the world of education, as functional staff should have high integrity to develop and improve the quality of human resources as a whole, both being able to participate in the KKG and experience making scientific papers when taking undergraduate studies . but it is not enough to stop there, but there are some perceptions that teachers are reluctant to be involved in publishing scientific papers due to very large costs, unsupportive school culture, only aimed at increasing credit numbers and limited practical support in preparing PTK reports and scientific articles . This paradigm is absolute that it is necessary to have reinforcement and habituation to educate teachers in the ability to write down problems in the teaching and learning process in schools. This perception made the research team move to create a special agenda for workshops on the identification of scientific writing and writing of paraphratic articles for teachers in SD Utama 2, Tarakan City.